Enhancing student satisfaction: evaluating on-campus haircut and grooming services with a focus on inclusivity and sustainability at UiTM - Affendy Lee, Noor Azli; Sulaiman, Suria; Rozli@Rosli, Mohd Ikmal Fazlan; Abd Ghani, Kay Dora; Ibrahim, Anas; Zaini, Intan Rabiatulainie (Universiti Teknologi MARA, Kedah, 2025)
This study evaluates student satisfaction and preferences regarding on-campus haircut and grooming services at a northern Universiti Teknologi MARA (UiTM) campus. Utilizing a mixed-methods approach, the research surveyed 155 students to explore their usage patterns, satisfaction levels, and interest in additional services and eco-friendly practices. The findings indicate that while most students appreciate the convenience of on-campus services, concerns about pricing, service quality, and inclusivity remain prevalent. Many students expressed a desire for more affordable pricing structures, improved barber skills through ongoing training, and a broader range of services that cater to diverse needs, including options specifically for female students. Additionally, there is significant interest in incorporating sustainable practices into grooming services, such as using organic and cruelty-free products. The study concludes with recommendations for enhancing the quality and accessibility of on-campus grooming services to better meet student needs and align with their values, ultimately contributing to higher satisfaction and a more supportive campus environment.